Design and implementation of a social networking platform for cloud deployment specialists. Issue 1 (August 2015) - Magoutis, Kostas; Papoulas, Christos; Papaioannou, Antonis; Karniavoura, Flora; Akestoridis, Dimitrios-Georgios; Parotsidis, Nikos; Korozi, Maria; Leonidis, Asterios; Ntoa, Stavroula; Stephanidis, Constantine
Abstract A new discipline at the intersection of the development and operation of software systems known asDevOps has seen significant growth recently. Among the wide range of tasks of DevOps professionals, we focus on that of selecting appropriate cloud deployments for distributed applications. Despite the advent of automated software deployment and management frameworks, reasoning about good deployments still requires interaction with experts, often through discussions on online technical forums and social networks. Current social networking technologies offer basic ways to communicate. Within theDevOps community, communication on application structure and cloud deployment tradeoffs could become more effective by using knowledge present in global community-sourced information repositories. In this paper we argue for the benefits of tapping into such knowledge and for seamlessly feeding it back into the social networking platform. The social networking platform presented in this paper integrates social networking with automated deployment of applications on multi-clouds and with knowledge drawn from community-sourced information repositories. The implementation leverages two such repositories, the PaaSage repository and Chef Supermarket. Our user evaluation experiments demonstrate the value created forDevOps professionals.